Achieving high bactericidal and antibiofouling activities of 2D titanium carbide (Ti3C2Tx) by delamination and intercalation. (13th June 2019) - Rajavel, Krishnamoorthy; Shen, Shuyi; Ke, Tao; Lin, Daohui
Abstract: The development of extrinsic antibacterial agents using newly identified nanoscale 2D layered transition metal carbide (MXene) was established by different delamination and intercalation approaches to explore structure-bioproperty relations. Herein, we report the potential impact of the microbial inactivation of Escherichia coli ( E. coli ) by delaminating (water, dimethyl sulfoxide (DMSO), and isopropylamine) and intercalating (hydrazine monohydrate (HMH), sodium hydroxide, and potassium hydroxide) of MXene (Ti3 C2 T x ), and its bactericidal mechanism was interpreted. The delaminations and intercalations all significantly increased the colloidal stability and bactericidal effect of Ti3 C2 T x suspensions via unpacking of stacked MXene layers, among which the HMH intercalation showed the best performance. Our experimental results reveal that the mechanism of bacterial killing was primarily because of surface wrapping followed by extracellular reactive oxygen species independent oxidative stress. This study also shows that the stacked layer separation along with the surface moiety is an essential and decisive factor that determines the lethal bacterial potency of Ti3 C2 T x . The application of Ti3 C2 T x -coated polyvinylidene fluoride (PVDF) membranes effectively inactivates E. coli ; importantly, it prevents biofilm formation on the active membrane surfaces and thus has high potential for antibiofouling. This study provides useful guidelines for the future development of Ti3 C2 T x -based antimicrobial surface coatings and increases their bioapplication potential.